2022
DOI: 10.1002/bse.3176
|View full text |Cite
|
Sign up to set email alerts
|

Price sensitivity, government green interventions, and green product availability triggers intention toward buying green products

Abstract: In the 21st century, environmental problems are wreaking havoc, and sustainability is now of primary importance. Several external factors like population growth, industrialization, development, and overexploitation of natural resources play a crucial role in environmental degradation. Thus, the present study endeavors to explore the impact of price sensitivity, governments green interventions and green product availability on green buying intention through the lenses of the theory of planned behavior and the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 126 publications
0
16
0
Order By: Relevance
“…A modified version of the TPB model can be used to study a particular context, for instance sustainable clothing consumption, by incorporating variables that help researchers study what motivates (or disincentives) sustainable behavior (Brandão and da Costa, 2021;Stern, 2000). Existing literature suggests that several constructs can be used for modifying the original model to study green purchasing behavior and sustainable consumption (Bigerna et al, 2021;Dangelico et al, 2021;Frommeyer et al, 2022;Onel, 2017;Si et al, 2022;Singh et al, 2021, Srivastava et al, 2022Yadav and Pathak, 2017;Yew et al, 2022;Zhang et al, 2019). For instance, the study by Kang et al (2013) modified the TPB and found that customers' perceived consumer effectiveness, product knowledge, and perceived personal relevance greatly affected the dimensions of the TPB, thus influencing the purchase intentions for environmentally sustainable clothing.…”
Section: Theory Backgroundmentioning
confidence: 99%
“…A modified version of the TPB model can be used to study a particular context, for instance sustainable clothing consumption, by incorporating variables that help researchers study what motivates (or disincentives) sustainable behavior (Brandão and da Costa, 2021;Stern, 2000). Existing literature suggests that several constructs can be used for modifying the original model to study green purchasing behavior and sustainable consumption (Bigerna et al, 2021;Dangelico et al, 2021;Frommeyer et al, 2022;Onel, 2017;Si et al, 2022;Singh et al, 2021, Srivastava et al, 2022Yadav and Pathak, 2017;Yew et al, 2022;Zhang et al, 2019). For instance, the study by Kang et al (2013) modified the TPB and found that customers' perceived consumer effectiveness, product knowledge, and perceived personal relevance greatly affected the dimensions of the TPB, thus influencing the purchase intentions for environmentally sustainable clothing.…”
Section: Theory Backgroundmentioning
confidence: 99%
“…This did not side up with the inferences of Yang et al (2022) and was contrary to our expectancies that sustainable luxury fashion might contribute to building social prestige. Further, a recent integrated TCV framework by Srivastava and Gupta (2023) articulates that subjective norms and social groups can stimulate a habitual inclination towards conventional green purchasing within a non‐Western culture (India). However, our empirical examination challenges the validity of this direct correlation in the context of sustainable luxury fashion, indicating potential variability in its generalizability.…”
Section: Discussion Of Main Findingsmentioning
confidence: 99%
“…These conceptualizations advance findings of recent works on the widely reported value‐action gap and sustainable luxury fashion paradox (e.g., Carranza et al, 2023; Essiz et al, 2023) by elucidating the theoretical pathway through which individual difference factors influence consumers' ability to translate their value perceptions into purchasing decisions. At the macro‐scale, our integrated TCV model goes beyond generic TCV applications (Biswas & Roy, 2015; Lin & Huang, 2012; Srivastava & Gupta, 2023) and adds to the latest movement on transformative luxury research (Kim et al, 2022; Pai et al, 2022), echoing the positivistic sentiment that sustainability and luxury can have a common future in fostering social‐environmental change among US consumers.…”
Section: Implications Limitations and Future Directionsmentioning
confidence: 99%
“…Yarimoglu and Gunay (2020) extended the model by introducing external factors such as pro‐environmental engagement and perceived image to explain consumers' visiting intention to green hotels. While investigating green product purchase intention, Srivastava and Gupta (2023) introduced price sensitivity, government intervention and product availability as moderators to the original TPB model. Similarly, to capture the complexity of real‐world behaviour and provide a more accurate picture of how behaviour is influenced, other variables, such as environmental concern (Li & Zhang, 2023; Yarimoglu & Binboga, 2019), narcissism (Yarimoglu & Binboga, 2019), moral norms (Liu et al, 2020; Roos & Hahn, 2017), consumer innovativeness and effectiveness (Siraj et al, 2022; Yarimoglu & Binboga, 2019), materialism (Bucher et al, 2016), religiosity (Singh et al, 2021) and ethical concern (D'Souza et al, 2022) were also incorporated into the model.…”
Section: Theoretical Backgroundmentioning
confidence: 99%